Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaanterhadap Kebijakan Deviden Perusahaan Manufaktur di BEI - Idawati, Ida Ayu Agung; Sudiartha, Gede Merta (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of profitability, liquidity and firm size either simultaneously or partially on the dividend payout ratio of manufacturing companies in the Stock Exchange in the period 2009-2011. Purposive sampling techniques used in sampling with the acquisition of as many as 31 companies as the study sample. This study used multiple linear regression as a data analysis technique. Simultaneously, all independent variables (profitability, liquidity, company size) affect the dividend payout ratio. Partial test showed that profitability and liquidity variables affect dividend payout ratio. Different results are shown by the variable size of the company, which does not affect the size of the company dividend payout ratio. Keywords: dividend payout ratio, profitability, liquidity, size of company